The Black Sea: A History - King, Charles, 1967-; Oxford University Press (New York : Oxford University Press, Incorporated, 2005)
The lands surrounding the Black Sea share a colorful past. Though in recent decades they have experienced ethnic conflict, economic collapse, and interstate rivalry, their common heritage and common interests run deep. Now, as a region at the meeting point of the Balkans, Central Asia, and the Middle East, the Black Sea is more important than ever. In this lively and entertaining book, which is based on extensive research in multiple languages, Charles King investigates the myriad connections that have made the Black Sea more of a bridge than a boundary, linking religious communities, linguistic groups, empires, and later, nations and states
Table Of Contents: Acknowledgments On Names List of Plates List of Maps An Archaeology of Place People and Water Region, Frontier, Nation Beginnings Geography and Ecology Pontus Euxinus, 700BC--AD500 The Edge of the World ``Frogs Around a Pond'' ``A Community of Race'' How a Scythian Saved Civilization The Voyage of Argo ``More Barbarous Than Ourselves'' Pontus and Rome Dacia Traiana The Expedition of Flavius Arrianus The Prophet of Abonoteichus Mare Maggiore 500--1500 ``The Scythian Nations are One'' Sea-Fire Khazars, Rhos, Bulgars, and Turks Business in Gazaria Pax Mongolica The Ship from Caffa Empire of the Comneni Turchia An Ambassador from the East Kara Deniz, 1500-1700 ``The Source of All the Seas'' ``To Constantinople---to be Sold!'' Domn, Khan, and Derebey Sailors' Graffiti A Navy of Seagulls Chernoe More, 1700--1860 Sea and Steppe A Flotilla on Azov Cleopatra Processes South The Flight of the Kalmoucks A Season in Kherson Rear Admiral Dzhons New Russia Fever, Ague, and Lazaretto A Consul in Trabzon Crimea Black Sea, 1860--1990 Empires, States, and Treaties Steam, Wheat, Rail, and Oil ``An Ignoble Army of Scribbling Visitors'' Trouble on the Kostence Line The Unpeopling ``The Division of the Waters'' Knowing the Sea The Prometheans Development and Decline Facing the Water Sources for Introductory Quotations Bibliography and Further Reading Index
Keywords: Black Sea Coast -- History; Black Sea Coast -- Politics and government; Black Sea Coast -- Civilization